Volksschauspiele Genese einer kulturgeschichtlichen Formation - Bernhart, Toni (Deutsche Literatur. Studien und Quellen, 2019)
Many types of works are characterized as folk plays: the peasant play, the passion play, the knightly drama, the tradition play, the mass festival, the anti-folk play, and the social drama. This book reconstructs the development of the folk play from the 18th century until today and puts into context the various forms it has taken. Textual examples from Johann Gottfried Herder to Elfriede Jelinek serve as illustration.